Transdermal iontophoresis patch with reverse electrodialysis. (1st January 2017) - Lee, Joon; Kwon, Kilsung; Kim, Minyoung; Min, Joonhong; Hwang, Nathaniel S.; Kim, Won-serk
Abstract: Reverse electrodialysis (RED) technology generates energy from the salinity gradient by contacting waters with different salinity. Herein, we develop the disposable skin patch using this eco-friendly energy. The current density, which can be controlled easily without special circuit, is enough to iontophoretic drug delivery. In vitro study, this iontophoretic system enhanced the transdermal delivery of peptide, which is difficult to penetrate the skin barrier by simple diffusion. We design the disposable iontophoretic skin patch using RED system and suggest this patch can be apply on new cosmetic patch or disposable drug patch.